Strapdown inertial navigation technology - Titterton, D. H. (IEE radar, sonar, navigation, and avionics series, 2004)
"This book sets out to provide a clear and concise description of the physical principles of inertial navigation, the associated growth of errors and their compensation. There is also detailed treatment of recent developments in inertial sensor technology and a description of techniques for implementing and evaluating such systems. This new edition includes a number of refinements covering sensor technology, geodesy and error modelling, plus new chapters on MEMS technology and inertial systems applications."--Jacket